Bandwidth IMPLEMENTASI MANAGEMENT BANDWIDTH DENGAN METODE QUEUE TREE BERBASIS MIKROTIK PADA BALAI BESAR PELATIHAN KESEHATAN JAKARTA - Aziz Setyawan Hidayat; Luthfi Nursubana; Yamin Nuryamin; Pas Mahyu Akhirianto; suleman suleman (Informatics and Computer Engineering Journal, 2021)
At the Jakarta Center for Health Training (BBPK), users of bandwidth for each access point or PC Client are very excessive resulting in unequal allocation of bandwidth for each client PC in the company. So that the network connection of some client PCs is very slow and cannot even access the internet network. For this reason, it is necessary to have good bandwidth management for the Jakarta BBPK network, such as using the Queue tree method with a mikrotik router via the Winbox application. One solution so that bandwidth can be maximally utilized and flexible or stable is to manage the bandwidth (Bandwidth management) available in the network, one of which is by limiting the bandwidth capacity usage of each access point or client PC. Thus, if there is a client accessing the internet that is interrupted, because each client already has a bandwidth capacity based on the limit of the package used to access the internet. Bandwidth management is needed on the network at BBPK Jakarta in order to evenly allocate bandwidth for each access point or PC Client and reduce the occurrence of excessive or unstable network traffic at the company